Exploring Ethical Decision-Making in Accounting: The Mediating Role of Moral Judgment Among Professional Accountants - Oktrivina, Amelia; Murni, Anggita Pramesti, Yetty (Program Pascasarjana STIE Amkop Makassar, 2024)
Purpose: This study investigates the roles of moral disengagement and moral self-efficacy in shaping ethical behavior among accounting students at a university in Jakarta. Research Design and Methodology: Data were collected from 223 participants using convenience sampling, a sample size considered adequate for quantitative analysis, and sufficient statistical power to detect meaningful relationships. The data were analyzed using moderated regression analysis (MRA) with JAMOVI. Findings and Discussion: The results indicate that higher levels of moral disengagement are associated with lower ethical standards. In contrast, greater moral self-efficacy is a protective factor, reducing these adverse effects. The interaction between the two constructs reveals that individuals with high moral self-efficacy demonstrate greater resilience to the negative impacts of moral disengagement. In contrast, those with low self-efficacy are more vulnerable. Implications: These findings underscore the importance of addressing moral disengagement and self-efficacy to promote ethical decision-making. Practical implications suggest that organizations implement targeted interventions, such as training programs to reduce moral disengagement and initiatives to enhance moral self-efficacy, fostering ethical resilience and integrity in individuals and workplace environments. Keywords: Moral disengagement; Moral self-efficacys; Ethical Decision-Making (EdM).